Oxidative Stress Is Associated With Diastolic Dysfunction in Women With Ischemia With No Obstructive Coronary Artery Disease - Mohamad Raad; Ahmed AlBadri; Janet Wei; Puja K. Mehta; Jenna Maughan; Adit Gadh; Louise Thomson; Dean P. Jones; Arshed A. Quyyumi; Carl J. Pepine; C. Noel Bairey Merz (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Women with signs and symptoms of ischemia and no obstructive coronary artery disease often have evidence of diastolic dysfunction. Oxidative stress (OS) is associated with cardiovascular risk factors and adverse outcomes. The relationship between systemic OS and diastolic dysfunction is unknown. Methods and Results A subgroup of women (n=75) with suspected ischemia and no obstructive coronary artery disease who had both cardiac magnetic resonance imaging and OS measurements were enrolled in the WISE‐CVD (Women Ischemia Syndrome Evaluation—Coronary Vascular Dysfunction) study. Left ventricular end‐diastolic pressure was measured invasively. Left ventricular end‐diastolic volume and peak filling rate were assessed using cardiac magnetic resonance imaging. Aminothiol levels of plasma cystine and glutathione were measured as markers of OS. Spearman correlation and linear regression analyses were conducted. The group mean age was 54±11 years, and 61% had a resting left ventricular end‐diastolic pressure >12 mm Hg. Cystine levels correlated negatively with the peak filling rate (r=−0.31, P=0.007) and positively with left ventricular end‐diastolic pressure (r=0.25; P=0.038), indicating that increased OS was associated with diastolic dysfunction. After multivariate adjustment including multiple known risk factors for diastolic dysfunction and cardiovascular medications, cystine levels continued to be associated with peak filling rate (β=−0.27, P=0.049) and left ventricular end‐diastolic pressure (β=0.25; P=0.035). Glutathione levels were not associated with indices of diastolic function. Conclusions OS, measured by elevated levels of cystine, is associated with diastolic dysfunction in women with evidence of ischemia and no obstructive coronary artery disease, indicating the role of OS in patients with ischemia and no obstructive coronary artery disease. Its role in the progression of heart failure with preserved ejection fraction should be explored further.